(untitled) (Asian Journal of Medical Sciences, 2024)
Background: Knowledge of basic life support (BLS) is one of the life-saving measures that every medical undergraduate student must possess. Aims and Objectives: This study focused on knowing the level of knowledge in fresh medical undergraduate entrants (knowledge A [KA]) and 3rdyear students with clinical exposure but no BLS training (knowledge B [KB]). We also assessed the knowledge in 1st-year students (retention A [RA]) soon after foundation course and compared it with retained knowledge after 6 months (retention B [RB]). Materials and Methods: This non-randomized multigroup cross-sectional study was done on medical undergraduate students in a tertiary care hospital attached to a medical school in South India. A validated questionnaire with 25 questions assessing knowledge of BLS was formulated and administered to 508 medical students. Results: After analyzing data in SPSS V24, the mean scores in KA and KB were 11.03±4.33 and 13.95±5.43, respectively, with a P<0.001 which was significant. Although both the scores were >50%, clinical exposure had some effect on mean scores in medical undergraduates. Mean scores in RA and RB were 23.16±5.09 and 16.17±6.97, respectively, with P<0.001 which was significant, implying less retention of knowledge in RB 6 months after BLS training. Conclusion: A foundation course introduced into the medical curriculum is essential and refresher courses should be conducted frequently to retain the knowledge of BLS as daily academic commitments can prevent retention of BLS knowledge.